SOME INTEGRAL INEQUALITIES THROUGH TEMPERED FRACTIONAL INTEGRAL OPERATOR - Gul, Erdal; Yalcin, Abdullatif (ANKARA UNIV, FAC SCI, 2024)
In this article, we adopt the tempered fractional integral operators to develop some novel Minkowski and Hermite-Hadamard type integral inequalities. Thus, we give several special cases of the integral inequalities for tempered fractional integrals obtained in the earlier works.
Keywords: Hermite-Hadamard type inequalities; Minkowski inequality; convex and concave functions; Riemann-Liouville integrals; tempered fractional integral; Mathematics